2011
DOI: 10.1136/aim.2010.002485
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Effect on Thermal Tolerance and Electrical Pain Threshold: A Randomised Controlled Trial

Abstract: Objective The aim of this study was to test whether acupuncture could modify the threshold of tolerance to thermal and electrical stimuli. Methods A randomised placebo-controlled single-blind trial was conducted in 36 healthy volunteers randomly distributed to control (no treatment), conventional acupuncture and sham acupuncture groups. The subjects were blind to the group allocation. The authors measured before and after treatment the pain threshold with the Painmatcher (Cefar Medical AB, Lund, Sweden) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Nineteen studies (22.4%) compared acupuncture to an inert control such as a placebo pill [26] , [42] , a waiting list [38] , [62] , [68] , or a period of rest [24] , [25] , [27] , [30] , [35] , [47] , [51] , [53] , [56] [59] , [85] , [99] . In 12 of these studies, acupuncture had a greater effect than the inert control procedure [24] [26] , [30] , [38] , [51] , [53] , [57] , [58] , [62] , [68] , [85] , while results of six studies indicate no or only a minor change of the respective sensory threshold in any of the study groups [27] , [42] , [47] , [56] , [59] , [99] . Results of one study were unclear .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen studies (22.4%) compared acupuncture to an inert control such as a placebo pill [26] , [42] , a waiting list [38] , [62] , [68] , or a period of rest [24] , [25] , [27] , [30] , [35] , [47] , [51] , [53] , [56] [59] , [85] , [99] . In 12 of these studies, acupuncture had a greater effect than the inert control procedure [24] [26] , [30] , [38] , [51] , [53] , [57] , [58] , [62] , [68] , [85] , while results of six studies indicate no or only a minor change of the respective sensory threshold in any of the study groups [27] , [42] , [47] , [56] , [59] , [99] . Results of one study were unclear .…”
Section: Resultsmentioning
confidence: 99%
“…Results of one study were unclear . One article reported a significant change of sensory thresholds after an inert control procedure [24] . All four studies evaluating acupuncture as an add-on treatment reported a significant additional effect [38] , [46] , [70] , [87] .…”
Section: Resultsmentioning
confidence: 99%
“…In nine other studies (18.8%) no effect was observed neither after verum nor after sham acupuncture [22, 27, 42, 47-49, 99, 103, 104], and the results of three studies (6.3%) were rated as unclear [35,44,45]. None of the twelve studies including both control modalities found significant differences between the sham and the inert control group [24,25,27,30,35,42,47,53,57,62,85,99], although in three of these studies, the pre-post comparison indicates larger effects in the sham than in the inert control group [24,30,53,85].…”
Section: Comparison Of Verum Acupuncture To Inert or Sham-control Promentioning
confidence: 92%
“…In ten studies (58.8%), the CPT was assessed by immersion of the subjects' fingers or forearm into ice-water and documenting either the time until subjects withdrew their limb [24,26,71] or the pain intensity that was experienced during a defined period of immersion into ice water [25, 56-59, 84, 89]. Eight of these ten studies (80%) showed a significant reduction of the CPT after acupuncture.…”
Section: Cold Pain Threshold (Cpt)mentioning
confidence: 99%
“…Interestingly, very few studies have investigated the effects of the number of acupuncture needles on experimentally-induced pain. Amand et al 15 found that acupuncture administered using five needles inserted to a depth of 12 mm with bidirectional rotation at verum points produced larger increases in electrical and heat pain thresholds compared with control but not compared with sham needling.…”
Section: Introductionmentioning
confidence: 99%